Transfusion Support for ABO-Incompatible Progenitor Cell Transplantation - Kopko, Patricia M. (Transfus Med Hemother, 2016)
ABO-incompatible transplants comprise up to 50% of allogeneic progenitor cell transplants. Major, minor and bidirectional ABO-incompatible transplants each have unique complications that can occur, including hemolysis at the time of progenitor cell infusion, hemolysis during donor engraftment, passenger lymphocyte syndrome, delayed red blood cell engraftment, and pure red cell aplasia. Appropriate transfusion support during the different phases of the allogeneic progenitor cell transplant process is an important part of ABO-incompatible transplantation.